Processes of cultural change and integration in the Roman world - Roselaar, Saskia T. (Mnemosyne, bibliotheca classica Batava. Supplementum. History and archaeology of classical antiquity ;, 2015)
"Processes of Cultural Change and Integration in the Roman World is a collection of studies on the interaction between Rome and the peoples that became part of its Empire between c. 300 BC and AD 300. The book focuses on the mechanisms by which interaction between Rome and its subjects occurred, e.g. the settlements of colonies by the Romans, army service, economic and cultural interaction. In many cases Rome exploited the economic resources of the conquered territories without allowing the local inhabitants any legal autonomy. However, they usually maintained a great deal of cultural freedom of expression. Those local inhabitants who chose to engage with Rome, its economy and culture, could rise to great heights in the administration of the Empire. Contributors are: Patricia Argüelles, Aitor Blanco-Peréz, Elisabeth Buchet, Christopher Burden-Strevens, Tamara Dijkstra, Leonardo Gregoratti, Maurizio Gualtieri, Alfred Hirt, Enora Le Quéré, Josipa Lulić, Daniele Miano, Alexander Rubel, Rafael Scopacasa, Christopher Sparey-Green, Marleen Termeer, and Fiona Tweedie"--